Optimal response to tislelizumab plus chemotherapy in metastatic triple-negative breast cancer: a case report and literature review - Ma, Yuxin; Shi, Xinhong; Zhao, Kun; Hu, Shuyi; Shi, Yue; Jiang, Yingying; Liu, Yiling; Lu, Lin; Chang, Yuting; Zhou, Fei; Dai, Yingying; Wu, Zipeng; et al. (Frontiers in Oncology, 2024)
Metastatic triple-negative breast cancer (mTNBC) has the worst prognosis among breast cancer subtypes. Immune checkpoint inhibitors (ICIs) plus chemotherapy have promising survival benefits. Herein, we report a 51-year-old woman whose metastatic lesions were diagnosed as triple-negative subtype and who received tislelizumab plus eribulin treatment and achieved excellent efficacy. To our knowledge, this study is the first attempt to present tislelizumab in combination with eribulin for mTNBC treatment. New treatments resulting in prolonged survival and durable clinical responses would benefit mTNBC patients. Then, we summarize the possible influencing factors of the interaction between tislelizumab and eribulin.